Odontogenic Maxillary Sinusitis: Etiological Pathways and Clinical Implications – A Contemporary Review - Potrykus, Maria; Musyt, Wiktoria; Pietruszka, Wiktoria; Klasicki, Przemysław (Quality in Sport, 2025)
Introduction: Odontogenic sinusitis (OS) constitutes a significant yet frequently underdiagnosed clinical entity at the intersection of dental and otorhinolaryngological disorders. The primary etiological factors include periapical lesions affecting the maxillary premolars and molars, as well as complications related to endodontic treatment. Cone beam computed tomography (CBCT) is crucial for accurate diagnosis, enabling detailed assessment of the anatomical relationship between the teeth and the maxillary sinus. Aim of the Study: The aim of this study is to present current diagnostic and therapeutic guidelines for odontogenic sinusitis, with an emphasis on the importance of interdisciplinary collaboration in achieving effective management and minimizing complications. Methods: A literature review was conducted based on the PubMed and Google Scholar databases using the keywords: „odontogenic sinusitis”, „chronic maxillary sinusitis”, „FESS”, „oroantral fistula”, „dental sinusitis treatment”. Conclusion: Effective management of odontogenic sinusitis requires an interdisciplinary approach, integrating elimination of the infectious source, restoration of sinus ostium patency, and tailored pharmacotherapy. Coordinated collaboration between dental and otorhinolaryngological specialists plays a key role in optimizing treatment outcomes and reducing the risk of complications.